Report of a Working Group on Sunflower (fourth meeting): held at the Facoltà di Agraria, Università degli Studi di Pisa, Italy, 11-12 May 1991 - International Board for Plant Genetic Resources; European Cooperative Programme for the Conservation and Exchange of Crop Genetic Resources (1992)
Report of the ECPGR Sunflower Working Group meeting, fourth meeting, 11-12 May 1991, Perugia, Italy